Predictor of Mortality in Acquired Immunodeficiency Syndrome Patients with Central Nervous System Opportunistic Infections - Agustina Lestari; Sofiati Dian; Chrysanti Murad (Althea Medical Journal, 2016)
Background: Indonesia’s increase of acquired immunodeficiency syndrome (AIDS) cases is one of the fastest. Mortality cases of AIDS also increase per year. Central nervous system (CNS) opportunistic infection is one of the most likely manifestations on advanced stage of Human immunodeficiency virus (HIV)/AIDS patients. Common CNS opportunistic infections are toxoplasma infection and tuberculous meningitis (TBM). The study aimed to analyze the predictor of mortality in AIDS patients with CNS opportunistic infections.Methods: This study reviewed 151 medical records from AIDS patients with CNS opportunistic infection admitted to the Department of Neurology, Dr. Hasan Sadikin General Hospital Bandung from 2007-2012. This study was conducted from April to November 2013. Patients’ clinical manifestations (seizure, headache, altered consciousness), laboratory examination (CD4+ level count) and treatment history (antiretroviral or ART and cotrimoxazole) were collected. Chi-square and logistic regression test were used to determine the mortality predictor in patients.Results: Mortality rate was 37.7%. Clinical manifestations from patients were seizure 29.8%, altered consciousness 66.2%, and headache 88.7%. Patients had cotrimoxazole treatment 44.4% and 38.4% patients had ART. CD4+ level count data from 86 patients were obtained, 94% had CD4+ level count ≤200. Bivariate analysis showed altered consciousness had significant mortality predictor (Odd ratio (OR): 29.944; 95% Confidence interval (CI) 6.9–129.945; p<0,0). Multivariate analysis showed ART had highest predictive mortality value (OR: 2.968; 95% CI 1.236–7.126; p=0.015).Conclusions: Altered consciousness and no antiretroviral treatment are mortality predictors in AIDS patients with CNS opportunistic infections. [AMJ.2016;3(4):577–82] DOI: 10.15850/amj.v3n4.942